2018
DOI: 10.1111/nmo.13381
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture via chronically implanted electrodes improves gastric dysmotility mediated by autonomic‐cholinergic mechanisms in a rodent model of functional dyspepsia

Abstract: Gastric motility (GSW and GE) is impaired in rats treated with IA, possibly attributed to impaired autonomic functions. EA improves GSW and accelerates GE mediated via the autonomic and cholinergic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 57 publications
3
17
0
Order By: Relevance
“…Accordingly, a pre‐experiment was performed to determine the EA stimulation amplitude that was tolerable by all rats and 2 mA was found to be the most suitable value. It was a well‐established set of parameters that had been proven effective in treating gastrointestinal motility and functional dyspepsia . With our methods (our specific parameters in animals and humans), electrical stimulation at non‐acupoints has been shown ineffective in altering gastrointestinal motility as shown in numerous previous studies .…”
Section: Methodsmentioning
confidence: 91%
“…Accordingly, a pre‐experiment was performed to determine the EA stimulation amplitude that was tolerable by all rats and 2 mA was found to be the most suitable value. It was a well‐established set of parameters that had been proven effective in treating gastrointestinal motility and functional dyspepsia . With our methods (our specific parameters in animals and humans), electrical stimulation at non‐acupoints has been shown ineffective in altering gastrointestinal motility as shown in numerous previous studies .…”
Section: Methodsmentioning
confidence: 91%
“…Evidence has shown that gastrointestinal diseases are accompanied by ANS dysfunction ( Zhang S. et al, 2018 ). By detecting 24-h HRV, gastrointestinal motility, and gastric acid secretion, Tominaga et al (2016) found that patients with functional dyspepsia had increased sympathetic tone and decreased vagal reactivity and that patients with ANS disorders had more serious gastrointestinal symptoms with higher indigestion scores.…”
Section: Acupuncture Is Effective In Alleviating Autonomic Nervous Sy...mentioning
confidence: 99%
“…The enhancement of vagal activity with EA/TEA was reported in several previous studies and considered as one of major mechanisms involved in the prokinetic effects of EA/TEA. 39,40 EA at ST36 was reported to improve gastric slow waves in a rat model of FD 39 and normalize impaired colonic motility induced by rectal distension in dogs 40 ; the prokinetic effects were inhibited by atropine, an antagonist of acetylcholine (Ach). 39,40 The increase in vagal activity was reported to be associated with the improvement of dyspepsia symptoms in FD patients with the TEA treatment at PC6 and ST36.…”
Section: Autonomic-endocrine Mechanisms Of Teamentioning
confidence: 99%
“…39,40 EA at ST36 was reported to improve gastric slow waves in a rat model of FD 39 and normalize impaired colonic motility induced by rectal distension in dogs 40 ; the prokinetic effects were inhibited by atropine, an antagonist of acetylcholine (Ach). 39,40 The increase in vagal activity was reported to be associated with the improvement of dyspepsia symptoms in FD patients with the TEA treatment at PC6 and ST36. 6 Moreover, vagal nerve activation has been reported to exert anti-inflammatory effects in several experimental and clinical studies.…”
Section: Autonomic-endocrine Mechanisms Of Teamentioning
confidence: 99%